Synthesis and pharmacological studies on a novel series of mast cell-stabilising tetrahydronaphthalenes and related compounds - Barlow, James William (Trinity College (Dublin, Ireland). School of Pharmacy & Pharmaceutical Sciences, 2003)
The purpose of this thesis was the design, synthesis and pharmacological screening of a novel series of tetrahydronapthalene molecules for mast cell-stabilising activity. The introductory Chapter commences with a discussion of mast cells and basophils as key effectors of the allergic response. The molecular mechanisms through which these cells are activated and degranulated are discussed, together with a synopsis of the chemical mediators of allergy released from them, both upon degranulation and those synthesised de novo. The consequences of pathological activation of the allergic cascade are then outlined, with an overview of both currently available and investigational therapies for these conditions, with especial emphasis on molecules derived from natural sources. The rationale for the screening of the target molecules is introduced, with reference to previously tested indan molecules and dimers thereof, and the biological activities of indan and tetrahydronaphthalene molecules reported to date is reviewed. Chapter 1 concludes with a discussion of the various pharmacological models of allergic disease that are utilised in candidate drug screening programmes.
Keywords: Pharmacognosy, Ph.D.; Ph.D. Trinity College Dublin